Analisis Pemberian Insentif dalam Upaya Meningkatkan Motivasi dan Kinerja Karyawan Studi Kasus Perusahaan Tour Travel PT. Amanah Safari Internasional di Lampung - Annisa Riska Yulinda; Hurian Kamela (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
The following study aims to analyze and find out (1) The impact of incentives on the work results of PT employees. Amanah Safari Internasional Tour Travel, which has been running, (2) This research uses a qualitative approach to look for incentives to improve the performance of PT employees. Amanah Safari International Travel. Data mining methods encompass observation, documentation, and direct interviews with management and relevant staff. The results of this study show (1) the incentive system that the company has to provide material and non-material incentives to its employees, such as bonuses and social security, religious and non-religious awards and joint holidays. Employee quality, employee quantity, and employee attendance or discipline drive employee performance and motivation. This research shows that incentives can increase work morale and increase achievement, loyalty, discipline, and accountability towards positions. These valuable results can have an impact on improving employee performance. (2) According to the analysis results, PT. Amanah Safari Internasional Tour Travel has an incentive program that suits the needs of its employees, but further research is needed to improve the efficiency of this program. As a result, companies are expected to be able to maintain and improve their incentive policies to improve employee performance.